Fast Scalable Robust Node Enumeration - Black, Richard; Donnelly, Austin; Gavrilescu, Alexandru; Thaler, Dave (Proceedings of 4th International IFIP-TC6 Networking Conference (NETWORKING 2005), 2005)
In a Local Area Network of computers, often a machine wants to learn of the existence of all the others satisfying some condition. Specifically, there are a number of existing discovery algorithms which permit an enumerator to reliably discover protocol participants, many of them idealised. This paper provides a new technique which controls the load placed on the network, minimises the time to completion, handles networks with significant loss, and scales over many orders of magnitude. Most significantly, the protocol also deals with the possibility of a malicious enumerator; an important contribution needed for current real-world networks. We also address the effects of several systems and engineering aspects, including scheduler jitter and clock quantisation.
To appear